EFFECT OF HULL AND ACCOMMODATION SHAPE ON AERODYNAMIC PERFORMANCES OF A SMALL SHIP - Toan, Ninh Cong; He, Ngo Van (Vietnam Journal of Marine Science and Technology, 2019)
In marine transportation, aerodynamic performance is important for the ships, especially for the small passenger fast ships. It has affected the service speed, air resistance acting on hull, power energy as well as roll, pitch, yaw and stability of the ships. Moreover, the aerodynamic performance also directly affects the passengers, captains or employments who work on the ships. For a bad aerodynamic performance hull shape, it may make an accident in marine transportation. In this paper, the authors present a study on effect of hull shape on aerodynamic performance of a small passenger fast ship by using a commercial Computational Fluid Dynamics (CFD). Several hull forms with different shapes are proposed and computed to show their aerodynamic performances. From the comparison between different CFD results of the ships, the effects of hull shape on aerodynamic performances of the ships are understood.